Theft on Thursday - Purser, Ann (New York : Berkley Prime Crime, 2006)
A friend has asked working-class mother and house cleaner Lois Meade to help crack a case. It looks like the handsome new choirmaster may have been poisoned. Soon, Lois finds herself untangling a web of secrets, bigotry, and intrigue-and can't let the culprits get away clean.
A Lois Meade mystery.
89155
Keywords: Meade, Lois (Fictitious character) -- Fiction; Cleaning personnel -- England -- Fiction; Country life -- England -- Fiction; Detective and mystery stories